Constraints Faced by Farmers in Utilizing Rice Related Information through Rice Knowledge Management Portal (RKMP) - Sunil Kumar , V. Sangeetha , Premlata Singh , R. Roy Burman , Arpan Bhowmik and S Arun Kuma, (Indian Journal of Extension Education, 2017)
Agriculture is a multifaceted enterprise comprising of millions of small and marginal farmers in India. Majority of Indianfarmers are resource poor and illiterate, having tiny or no access to present-day contemporary technologies. Information,knowledge and technologies available to millions of rural families determine the success in agriculture and ruraldevelopment. Rice Knowledge Management Portal (RKMP) is an initiative of Indian Institute of Rice Research (IIRR),Hyderabad, to cater to the information need of the stakeholders and provide a one-stop solution to all rice relatedinformation. The present investigation was undertaken with an objective to analyse the constraints faced by farmers inutilising the information available through RKMP. The results showed that farmer face technological, social andpsychological constraints more severely. Among the technological constraints ; lack of updated information' was stoodfirst (mean rank=6.388) in utilizing the information. Similarly, electricity problem (mean rank =5.350) and poorconnectivity (mean rank =4.831) were also considered as limiting factors among farmers. In case of social constraints'lack of access to women farmers' (mean rank =3.731) found to be the most limiting factor for using portal information.Similarly 'lack of institutional support' (mean rank =3.631) and 'less networking among farmers (mean rank =2.813) werealso affected significantly. In case of psychological factors 'techno-phobia'(mean rank =2.219) was found most severe.Lack of motivation (mean rank =1.794) was least affecting to information management and delivery. Among economicalconstraints, cost of computer/smart phone (mean rank= 1.513) was affecting utilization of information provided by portal.The finding will be helpful in redesigning and modifications needed for reaching upto the grass root level fordisseminating information and making portal more effective for farmers for timely and relevant information